Gasto público del sector salud y pobreza monetaria en la región Loreto periodo 2014 - 2019 - Arteaga Chamba,Silvia Athaiz (2021)
The research aims to verify the incidence of public spending in the health sector with respect to monetary poverty in the Loreto region for the period 2014 - 2019. In the theoretical framework, you can learn more about the indicators used in the research through of its different theories and antecedents that give solidity to the study. The data was obtained by collecting data on the subject studied from the reports and reports of the National Institute of Statistics and Informatics and the Ministry of Economy and Finance; For this, it was analyzed using the statistical programs Minitab and SPSS, for the validation of the hypothesis, the parametric statistical test ANOVA was applied. The result obtained from the statistical test was at a confidence level of 95% and an absolute error of 5%, it was obtained as a result that P-Value is 0.000, less than 0.05; Therefore, it is accepted that public spending in the health sector affects the reduction of monetary poverty in the Loreto region in the period 2014 - 2019.